Study on the grain refinement mechanism of Mg-Al alloy based on carbon addition. - Lifeng Sun; Zhongyu Gao; Zhongchao Hu; Huyan Chen; Jianwen Cai; Xiaoou Cai (PLoS ONE, 2022)
In this study, a comprehensive treatment process based on the rotary injection of Ar+CO2 Mg-Al alloy melt is proposed. The effect of carbon on the grain refinement of Mg-Al alloy is studied according to the proposed integrated treatment process. The regularity of carbon refinement in the Mg-Al alloy is examined by microstructural observation and theoretical calculation. The results show that carbon has no effect on the grain refinement of Mg-Al alloy when the Al content is less than 1wt.%. However, when the Al content reaches 2 wt.%, the refining effect is obvious, and the grain refinement efficiency is 62%. The refining effect increases with the increase in the Al content, and the refinement efficiency becomes 79% when the Al content reaches 9 wt.%. The size of Al-C-O in the matrix is approximately 5μm, which confirms the existence of Al4C3 phase exists as a heterogeneous nucleating agent. The theoretical calculations suggest that the Al4C3 heterogeneous nucleating agent cannot be formed when the Al content in the Mg alloy is less than 1.34%, so there is no thinning effect under such Al content. The crystallographic calculations reveal that the mismatch between the Al4C3 phase and Mg alloy matrix is only 4.05%, and Al4C3 can exist as a heterogeneous nucleating agent for α-Mg phase. Combining the measured solidification curves with the classical nucleation theory, the wetting angle of Mg-Al alloy on Al4C3 is calculated to be 24.3°.